COASTAL GEOMORPHOLOGICAL FEATURES AND GEOARCHAEOLOGICAL POTENTIAL OF KAVOURI BAY, ATTICA, GREECE - Vandarakis, D.; Pavlopoulos, K.; Kapsimalis, V. (Bulletin of the Geological Society of Greece, 2016)
The discovery of a paved Hellenistic road, which was ended at the shoreline of the Megalo Kavouri bay in Attica, Greece, led the archaeologists to hypothesize that an ancient harbour would be located somewhere at the adjacent submarine area. For the identification of the position of this harbour, a joint submarine and littoral geomorphological survey was carried out. The oceanographic mission was conducted in order to map the underwater landforms. A variety of geomorphological characteristics, types of substrate and habitats (i.e., rocky outcrops, boulder or gravel accumulations etc.) and anthropogenic objects (i.e., debris of recent construction material) were identified in the shallow water seabed of the Kavouri Bay. The littoral geomorphological survey was carried out to determine the natural processes affecting the continental part of the area and map the coastal landscape features. Data derived by both submarine and littoral geomorphological investigations indicate that the most probable location of the harbour could be situated in the southern part of the study area.